Evaluation of development performance of port cluster: the case of Yangtze River Delta port cluster - Wang, Jie; Zhang, Yan; Lu, Xin (Frontiers in Marine Science, 2025)
Since the last round of government-led provincial port reforms, China’s port clusters have developed rapidly. Despite being China’s most significant port cluster, the Yangtze River Delta (YRD) port cluster faces certain constraints in its development process, which hinder it from fully realizing its potential. This paper aims to clarify the advantages and constraints of the Yangtze River Delta port cluster development through a comprehensive and systematic evaluation, which is crucial for optimizing the cluster’s collective efficiency and effectiveness. Therefore, further deepening of reform is needed, which requires a comprehensive evaluation of the development performance of the port cluster. This study develops a port cluster evaluation model (S = P × k), where S = score, P = competitiveness (hard power), and k = harmony coefficient (system coordination). The framework follows three principles: functional differentiation, hierarchical decomposition (macro to micro), and dynamic equilibrium. The indicator system includes two Level-1 metrics—Overall competitiveness (4 sub-indicators, e.g., economic scale) and System harmony (2 sub-indicators, e.g., cooperation-competition balance)—plus 10 Level-3 operational indicators (e.g., cargo throughput). Weights are determined via AHP, combining objective and subjective methods. Subsequently, the developmental level and overall performance of the Yangtze River Delta port cluster are assessed with the evaluation model. The evaluation results show a clear performance hierarchy: Shanghai port cluster leads (0.230), preceding Zhejiang (0.178) and Jiangsu (0.127), whereas Anhui (0.020) occupies the lowest position. The evaluation results reveal three significant findings. First, the harmony coefficient (k) demonstrates a particularly strong influence on the comprehensive scores. Second, the 0.230-0.020 performance range across provincial clusters quantitatively validates the YRD’s development imbalances. Third, our three-tier indicator system successfully identifies under performing dimensions at different levels (e.g., Anhui’s weak Level-3 operational indicators). In light of the evaluation outcomes and the actual development status, optimization strategies (such as enhance planning and coordination, promote port cooperation, clarify port positioning and division of labor) are proposed to address the existing problems in this large port cluster.